Dysregulation of metabolic‐associated pathways in muscle of breast cancer patients: preclinical evaluation of interleukin‐15 targeting fatigue. Issue 4 (26th March 2018) - Bohlen, Joseph; McLaughlin, Sarah L.; Hazard‐Jenkins, Hannah; Infante, Aniello M.; Montgomery, Cortney; Davis, Mary; Pistilli, Emidio E.
Abstract: Background: Breast cancer patients report a perception of increased muscle fatigue, which can persist following surgery and standardized therapies. In a clinical experiment, we tested the hypothesis that pathways regulating skeletal muscle fatigue are down‐regulated in skeletal muscle of breast cancer patients and that different muscle gene expression patterns exist between breast tumour subtypes. In a preclinical study, we tested the hypothesis that mammary tumour growth in mice induces skeletal muscle fatigue and that overexpression of the cytokine interleukin‐15 (IL‐15) can attenuate mammary tumour‐induced muscle fatigue. Methods: Early stage non‐metastatic female breast cancer patients ( n = 14) and female non‐cancer patients ( n = 6) provided a muscle biopsy of the pectoralis major muscle during mastectomy, lumpectomy, or breast reconstruction surgeries. The breast cancer patients were diagnosed with either luminal (ER + /PR +, n = 6), triple positive (ER + /PR + /Her2/neu +, n = 5), or triple negative (ER − /PR − /Her2/neu −, n = 3) breast tumours and were being treated with curative intent either with neoadjuvant chemotherapy followed by surgery or surgery followed by standard post‐operative therapy. Biopsies were used for RNA‐sequencing to compare the skeletal muscle gene expression patterns between breast cancer patients and non‐cancer patients. The C57BL/6 mouse syngeneic mammary tumour cell line, E0771, was used to induce mammary tumours in immunocompetent mice, and isometric muscle contractile properties and fatigue properties were analysed following 4 weeks of tumour growth. Results: RNA‐sequencing and subsequent bioinformatics analyses revealed a dysregulation of canonical pathways involved in oxidative phosphorylation, mitochondrial dysfunction, peroxisome proliferator‐activated receptor signalling and activation, and IL‐15 signalling and production. In a preclinical mouse model of breast cancer, the rate of muscle fatigue was greater in mice exposed to mammary tumour growth for 4 weeks, and this greater muscle fatigue was attenuated in transgenic mice that overexpressed the cytokine IL‐15. Conclusions: Our data identify novel genes and pathways dysregulated in the muscles of breast cancer patients with early stage non‐metastatic disease, with particularly aberrant expression among genes that would predispose these patients to greater muscle fatigue. Furthermore, we demonstrate that IL‐15 overexpression can attenuate muscle fatigue associated with mammary tumour growth in a preclinical mouse model of breast cancer. Therefore, we propose that skeletal muscle fatigue is an inherent consequence of breast tumour growth, and this greater fatigue can be targeted therapeutically.